Assessment of children's independent mobility variables by mixed method. (November 2020) - Zarghami, Esmeail; Bagheri, Hossein
Abstract: In normative studies, which provide qualitative result to promote children's independent mobility (CIM), enough attention is not paid to the attitudes of children, parents and experts. Positive research that investigates CIM using measuring instruments, the researcher understanding of the study context and perceptual characteristics of children and parents is limited. The present study aims at investigating the variables of CIM using exploration and confirmatory methods, respectively. Analysis of 1896 behavioral places made possible discovering 9 selected ranges of independent mobility and 4 principles related to the promotion of CIM. Expert attitudes were assessed by Delphi technique and the exploratory principles were ranked by Shannon's entropy. Factor analysis was used to confirm the effect of 5 factors on improving CIM ( N  = 204). The housing type, number of floors, level of residency, street type, green-space, perceived safety and gender differences were variables related to CIM. Highlights: Exploration of normative principles of CIM through behavioral maps is necessary but is not sufficient. The normative principles can be insignificant for children. The low number of positive variables affected CIM. The reliance of CIM studies on any of the normative principles or positive factors is not enough. Using mixed method research by various measurement tools has been proposed.